PENDEKATAN TASAWUF DAN PSIKOTERAPI PERSPEKTIF ISLAM - Mursalin, Mursalin (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
The purpose of this study is to recognize Sufism and its history, understand the meaning of Islamic psychotherapy, and explore the role of Sufism in Islamic psychotherapy. In this research, the author used a literature review method with a qualitative approach. The result of this study is that Sufism is a spiritual practice that aims to understand the essence of faith and the Quran, cleanse the soul, improve morality, and get closer to Allah through the guidance of the Quran and Sunnah. Sufism has a significant role in Islamic psychotherapy by providing effective spiritual methods to cleanse the soul, improve morals, and achieve inner peace and happiness. Practices such as dhikr, tafakkur and muraqabah help individuals overcome bad traits and form good character. With a focus on values such as sincerity, patience, gratitude, tawakkal, and repentance, Sufism offers a comprehensive approach to healing the soul and providing inner peace through a close relationship with Allah. From the results of the research conducted, the author concludes that Sufism plays a role in helping to overcome psychological and emotional disorders by providing true peace and happiness through an approach to Allah subhanahu wa ta'ala